2020
DOI: 10.1111/jan.14456
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease perceptions of caregivers, adolescent, and adult patients: Barriers and facilitators to medical care adherence

Abstract: AimsTo provide an understanding of medical care adherence factors as reported by caregivers, adolescent, and adult patients with sickle cell disease and to analyse those concerns to identify barriers and facilitators about medical care adherence. Three topics influenced medical care adherence: the disease itself, therapeutics, and the healthcare system. This study will focus on the first topic.DesignQualitative explorative study, using semi‐structured and life‐experience interviews and manual inductive content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The DREPADO project is the first RCT designed to assess the impact of a paediatric-adult transition programme. The latter is based on the available literature [3] and on a recent previous qualitative study [10]. In accordance, it involves both paediatric and adult departments of care by starting the intervention in a paediatric department and continuing it in adult department of care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The DREPADO project is the first RCT designed to assess the impact of a paediatric-adult transition programme. The latter is based on the available literature [3] and on a recent previous qualitative study [10]. In accordance, it involves both paediatric and adult departments of care by starting the intervention in a paediatric department and continuing it in adult department of care.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, it involves both paediatric and adult departments of care by starting the intervention in a paediatric department and continuing it in adult department of care. In addition, the qualitative study found that the needs of parents and patients were biopsychosocial, both individual and familial [10]. Added to that, the modifiable factors of the SMART [11,12] were included in the 3 axis of the programme, to become patients' coping skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While previous studies have identified barriers to accessing care for adults with SCD, less is understood about the barriers that affect the pediatric SCD patient population [14]. Furthermore, there is limited data regarding barriers for those living in the Midwest, specifically in rural and medically under-resourced communities [1,15,16]. Telemedicine, the remote provision of medical care using real-time audio-visual consultation, is a valuable solution to addressing physician shortages and geographic barriers faced by patients and has proven successful for consultations in a variety of pediatric specialties [17].…”
Section: Introductionmentioning
confidence: 99%